2016
DOI: 10.1002/app.44507
|View full text |Cite
|
Sign up to set email alerts
|

Solubility measurement of hydrogen, ethylene, and 1‐hexene in polyethylene films through an intelligent gravimetric analyzer

Abstract: The solubility of hydrogen (H 2 ), ethylene (C 2 H 4 ), 1-hexene (C 6 H 12 ), and the mixture of C 2 H 4 /1-C 6 H 12 in semicrystalline polyethylene (PE) films is measured using an intelligent gravimetric analyzer (IGA) in combination with prediction equations. For the pure-component sorption in PE, the solubility of C 2 H 4 and 1-C 6 H 12 decreases with the temperature, while that of H 2 exhibits an opposite variation tendency in the temperature range under test. For the C 2 H 4 /1-C 6 H 12 mixture, the co-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…They showed that the solubility of ethylene in ternary systems is higher than its solubility in binary system. Other authors showed the same effect in the presence of co-monomers in ternary systems 13,22,23 . Chmelar et al 14 showed that the sorption of 1-hexene increases ethylene solubility in the amorphous PE.…”
Section: Introductionsupporting
confidence: 53%
“…They showed that the solubility of ethylene in ternary systems is higher than its solubility in binary system. Other authors showed the same effect in the presence of co-monomers in ternary systems 13,22,23 . Chmelar et al 14 showed that the sorption of 1-hexene increases ethylene solubility in the amorphous PE.…”
Section: Introductionsupporting
confidence: 53%
“…It was shown as early as 1957 that when two penetrants are solubilized in polyethylene, the heavier one enhances the solubility of the lighter one . If one considers the simplified case of a polymer and two penetrants, for instance ethylene and an ICA, the higher the concentration of the ICA, the higher the ethylene concentration will be in the amorphous fraction of the polyethylene . Obviously this should have an impact on a certain number of values, in particular the molecular weight distribution and the rate of polymerization.…”
Section: Impact Of Ica On Properties Rate and Other Important Issuesmentioning
confidence: 99%
“…In Figure , the hydrogen solubility in PE as calculated by the S–L EOS (with a degree of crystallinity equal to 0.224) is compared with experimental measurements at different pressures and temperatures . Apparently, there is an excellent agreement between predicted and experimentally measured solubility values.…”
Section: Dynamic Mass and Energy Balances For A Slurry‐phase Series Omentioning
confidence: 81%